1995
DOI: 10.1097/00000542-199506000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic Model Selection for Target Controlled Infusions of Propofol

Abstract: Although it may be preferable to administer propofol TCI by using a locally derived parameter set, it is acceptable to use a model from elsewhere. The Marsh and Tackley models produced equally good performance and are appropriate for propofol TCI within the range of 3-6 micrograms/ml. The Dyck model was less accurate at maintaining anesthetic concentrations, possibly because it was derived from low concentrations. Concentrations in blood, the most sensitive indicators of performance, demonstrated differences a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
54
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 238 publications
(56 citation statements)
references
References 28 publications
2
54
0
Order By: Relevance
“…Although no reference values have been reported for divergence or wobble, it has been suggested that the performance of a computer-assisted target-controlled infusion is acceptable for clinical use in patients if the bias is not greater than ±15–20 per cent and the inaccuracy is less than 30–40 per cent (Coetzee and others 1995, Swinhoe and others 1998, Van den Niewenhuyzen and others 2000, Egan 2003). Assessed on these criteria, the accuracy of the TCI device programmed with the final PK model can be considered appropriate for targeted delivery of propofol in healthy adult cats.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although no reference values have been reported for divergence or wobble, it has been suggested that the performance of a computer-assisted target-controlled infusion is acceptable for clinical use in patients if the bias is not greater than ±15–20 per cent and the inaccuracy is less than 30–40 per cent (Coetzee and others 1995, Swinhoe and others 1998, Van den Niewenhuyzen and others 2000, Egan 2003). Assessed on these criteria, the accuracy of the TCI device programmed with the final PK model can be considered appropriate for targeted delivery of propofol in healthy adult cats.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, during the later stages of anaesthesia, errors were not increased by subsequent passage of infusion time, as supported by the negative value of median divergence for the TCI-2 group. The usefulness of TCI lies in its potential ability to accurately maintain and to make proportional changes to blood drug concentrations (Coetzee and others 1995, Swinhoe and others 1998, Van den Niewenhuyzen and others 2000). Variability among individuals should always be expected, and titration of the target Cp to achieve the desired effect is essential in order to optimise intraoperative conditions and ensure the appropriate drug concentrations for rapid awakening.…”
Section: Discussionmentioning
confidence: 99%
“…Since the PBPK analysis (see below) is consistent with a value of about 0.022, this was the value that was assumed for standard values for freepl (freepl st ). The reported values for the normal human blood/plasma ratio (rblpl st ) vary from 1.1 to 1.3: [18,19,29,30] and a standard value of the blood/plasma ratio (rblpl st ) of 1.0 was assumed.…”
Section: Methodsmentioning
confidence: 99%
“…Several of these reports indicate that at low concentrations ω-3 PUFAs (10 to 100 μM) produce anticancer effects through the induction of apoptosis rather than via cytotoxicity. Propofol (2,6 diisopropylphenol) is the most extensively used general anesthetic-sedative agent employed today [18,19] and is nontoxic to humans at high levels (3 to 8 μg/ml; 20 to 50 μM) [20]. Propofol is a potent antioxidant [21-24] and has been shown to stimulate protein kinase C [25,26], inhibit calcium entry in muscle cells [27] and increase the calcium sensitivity of myofilaments in ventricular myocytes [28].…”
Section: Introductionmentioning
confidence: 99%